2022
DOI: 10.3390/ijms23179982
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Molecular Improvement for Potato Tuber Traits

Abstract: Potato is an important crop due to its nutritional value and high yield potential. Improving the quality and quantity of tubers remains one of the most important breeding objectives. Genetic mapping helps to identify suitable markers for use in the molecular breeding, and combined with transgenic approaches provides an efficient way for gaining desirable traits. The advanced plant breeding tools and molecular techniques, e.g., TALENS, CRISPR-Cas9, RNAi, and cisgenesis, have been successfully used to improve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 117 publications
1
9
0
Order By: Relevance
“…Several approaches are employed to achieve this goal. However, the conventional breeding approach, agronomic biofortification, transgenic approach, CRISPER technology, and reverse genetic approaches such as Association mapping and the quantitative trait loci (QTL) method are found to be effective in enhancing the nutrient content in potatoes [26,77,78].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several approaches are employed to achieve this goal. However, the conventional breeding approach, agronomic biofortification, transgenic approach, CRISPER technology, and reverse genetic approaches such as Association mapping and the quantitative trait loci (QTL) method are found to be effective in enhancing the nutrient content in potatoes [26,77,78].…”
Section: Discussionmentioning
confidence: 99%
“…Association Mapping and Quantitative Trait Loci (QTL) Association mapping and quantitative trait loci (QTL) analysis are two genetic approaches used in fortification programs to identify and understand the genetic factors influencing the levels of specific nutrients or compounds in crops [78]. The first one, Association mapping, also known as genome-wide association study (GWAS), involves studying the association between genetic variations (typically single nucleotide polymorphisms, or SNPs) and specific traits or characteristics.…”
Section: Marker-assisted Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors affect genomic accuracy, including marker set, population structure, genomic selection method, and trait genetic architecture. Research has shown that GP is highly or moderately accurate for quantitative characteristics in barley 41 , maize 42 , rice 43 , oat 44 , and wheat 20 , 39 .…”
Section: Introductionmentioning
confidence: 99%
“…Potato is an important crop due to its nutritional value and high yield potential, and is also considered a global food security crop. Genome editing will provide efficient and rapid technical approaches for targeted trait improvement and precise molecular breeding in potato ( Ye, Li & Ming, 2020 ; Ahmad et al, 2022 ; Tuncel & Qi, 2022 ). Our previous work showed that knocking out the self-incompatibility gene S-RNase by using the CRISPR/Cas9 system could create self-compatible diploid potato, which opens new avenues for diploid potato breeding and will also be useful for studying other self-incompatible crops ( Ye et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%